The Therapeutic Potential of Mangosteen Pericarp as an Adjunctive Therapy for Bipolar Disorder and Schizophrenia - Ashton, Melanie M.; Dean, Olivia M.; Walker, Adam J.; Bortolasci, Chiara C.; Ng, Chee H.; Hopwood, Malcolm; Harvey, Brian H.; Möller, Marisa; McGrath, John J.; Marx, Wolfgang; Turner, Alyna; Dodd, Seetal; et al. (Frontiers in Psychiatry, 2019)
New treatments are urgently needed for serious mental illnesses including bipolar disorder and schizophrenia. This review proposes that Garcinia mangostana Linn. (mangosteen) pericarp is a possible adjunctive therapeutic agent for these disorders. Research to date demonstrates that neurobiological properties of the mangosteen pericarp are well aligned with the current understanding of the pathophysiology of bipolar disorder and schizophrenia. Mangosteen pericarp has antioxidant, putative neuroprotective, anti-inflammatory, and putative mitochondrial enhancing properties, with animal studies demonstrating favorable pharmacotherapeutic benefits with respect to these disorders. This review summarizes evidence of its properties and supports the case for future studies to assess the utility of mangosteen pericarp as an adjunctive treatment option for mood and psychotic disorders.